Long-term trends in international migration: lessons from macroeconomic model - Docquier, Frédéric D (Economics and Business Review, 2018)
In this paper I develop a stylized model of the world economy and use it to explain the long-run trends in international migration. The model very well fits the trends of the last 40 years which are mainly governed by the evolution of population disparities between industrialized and developing countries. Then I provide migration projections for the 21st century and show that future migration is also governed by socio-demographic changes. I predict a robust increase in immigration pressures from sub-Saharan Africa and MENA countries to European countries.